Sustainable viticulture: how to evaluate and record it on a wine estate - Frederic Zahm (International Viticulture and Enology Society, 2021)
Sustainable viticulture is being developed to meet the challenges of current societal expectations. Numerous assessment tools have emerged in recent years. The IDEA method (Indicateurs de Durabilité des Exploitations Agricoles or Farm Sustainability Indicators) is one of these assessment tools. Using the 4th version of IDEA (IDEA4), this article assesses the overall performance (level of sustainability) of a wine estate in Bordeaux in partnership with the company Ekylibre.